Rating assessment of the sustainable development of the Russian entities: a scientific approach (Nexo Revista Científica, 2022)
The relevance of the present study is due to the socio-environmental crisis phenomena, the tool to minimize which is the transition to sustainable development, declared by the President of Russia. The article deals with the problem of assessing the level of sustainable development of the Far Eastern territories of the Russian Federation in terms of compliance with environmental goals of sustainable development of the UN 11-15. The authors use methods of graphic analysis, construction of time series and rating evaluations to assess the level of sustainable development in terms of environmental protection indicators in the subjects of the Russian Far East. As a result of defining the criteria according to the developed scale, the authors conclude that only in 2 regions the level is defined as favorable. The environmental problems of the regions are noted, and the key directions of improving the environmental well-being of the territories under consideration are outlined. As a result, it is determined that the key to solving these problems can be introducing elements of circular economy in the modern economic system.